Self-reported oral health among a community sample of people experiencing social and health inequities: cross-sectional findings from a study to enhance equity in primary healthcare settings. Issue 12 (23rd December 2015) - Wallace, Bruce; Browne, Annette J; Varcoe, Colleen; Ford-Gilboe, Marilyn; Wathen, Nadine; Long, Phoebe M; Parker, Joanne
Abstract : Objective: To describe the self-reported oral health issues among a community sample of primary care clients experiencing socioeconomic disadvantages. Methods: As part of a larger mixed-methods, multiple case study evaluating an equity-oriented primary healthcare intervention, we examined the oral health of a sample of 567 people receiving care at four clinics that serve marginalised populations in two Canadian provinces. Data collected included self-rated oral health and experiences accessing and receiving healthcare, standard self-report measures of health and quality of life, and sociodemographic information. Results: The prevalence of self-rated poor oral health was high, with almost half (46.3%) of the participants reporting poor or fair oral health. Significant relationships were observed between poor oral health and vulnerabilities related to mental health, trauma and housing instability. Our findings suggest that the oral health of some Canadian populations may be dramatically worse than what is reported in existing population health surveys. Conclusions: Our findings reinforce the importance of addressing oral health as part of health equity strategies. The health and oral health issues experienced by this client cohort highlight the need for interdisciplinary, team-based care that can address the intersections among people's health status, oral health and social issues.